Measurement of Student Satisfaction Using Customer Satisfaction Index (CSI) - Ragil Pardiyono; Hermita Dyah Puspita (Kusuma Negara Business School, 2020)
This study will measure the level of student satisfaction at a university in Bandung using a service quality model and student satisfactory inventory model. The measuring instrument used was a questionnaire with a sample of 100 respondents. Testing of measuring instruments by comparing the calculated r value (corrected item total correlation) with the r table. Reliability testing uses alpha values with table alpha values. Measuring the level of satisfaction using the customer satisfaction index (CSI). The results showed a CSI score of 94.04, which means that student satisfaction with campus services is very satisfied.